Heat and salt fluxes in the West Spitsbergen Current area in summer - Jan Piechura; Robert Osiñski; Tomasz Petelski; S³awomir B. Wo¼niak (Oceanologia, 2002)
Fluxes of radiation, sensible and latent heat, and fluxes of heat and salt within the upper layer of the ocean were calculated on the basis of measurements carried out in the area of the Norwegian-Atlantic and West Spitsbergen Currents during summer 2000.      The sea surface radiation balance was calculated from direct measurements of downward and upward short-wave (solar) radiation, the net radiation fluxes and sea surface temperature. The daily doses of radiation energy reaching and leaving the sea surface were also estimated.      To calculate the vertical heat fluxes in the atmospheric boundary layer the bulk parameterisation method was used. In most cases, the calculated heat fluxes were rather low, the average sensible heat flux was c. 10 W m-2, and the latent heat flux about one order of magnitude higher; this is what could be expected in summer. Salt fluxes to the air in the process of aerosol production are very small and can be neglected.      In summer the highest quantities of heat and salt are exchanged during mixing with surrounding waters.      According to our measurements, Atlantic Water on its northward course from about 70oN to 79oN loses about 100 TW of heat and 900 × 103 kg of salt. We thought it could be interesting to find out what happens to them. Some preliminary results of our investigation are presented here.